Antifungal screening of 61 folkloric medicinal plant extracts against dermatophytic fungi Trichophyton rubrum - P. Shivakumar Singh, G. M. Vidyasagar (Journal of Applied Pharmaceutical Science, 2015)
A series 305 extracts from 61 traditional medicinal plants (belonging to 33 different families) used in treating skin diseases in Hyderabad Karnataka region were subjected to antidermatophytic screening against Trichophyton rubrum (MTCC 1344). Pet ether, chloroform, ethyl acetate, methanol and aqueous extracts of each plant were tested for their antifungal activity using agar well diffusion method at sample concentration of 5 & 2.5 mg/ml. The results indicated that out of 61 plants, 18 exhibited very effective antidermatophytic activity in methanolic extracts, effective activity observed in 13 plants in different extracts, whereas 26 plants showed moderate activity, 04 plants showed weak activity. The minimum inhibitory concentrations of 18 very effective plants were determined. On the basis of the results obtained, the crude extracts of Allium sativam Linn., Annona reticulata L., Annona squamosa L., Argemone mexicana L., Butea monosperma, Ceasalpinia bonducella, Citrus medica L., Corchorus oleterius L., Emblica officinalis, Euphorbia tirucalli L., Ficus racemosa L., Gymnosporia montana, Lawsonia inermis L., Solanum nigrum L., Sterculia foetida L., Tribulus terrestris L., Vitex negundo L., and Zingiber officinale exhibited significant antidermatophytic activity (T. rubrum) and properties that support folkloric use in the treatment of skin diseases as broad-spectrum antimycotic agents. This probably explains the use of these plants by the indigenous people against dermatological infections.
Keywords: Folkloric medicinal plants, Trichophyton rubrum, antifungal screening.